A separate peace - Knowles, John, 1926-2001 (Scribner, 2003)
Set at a boys' boarding school in New England during the early years of World War II, A Separate Peace is a harrowing and luminous parable of the dark side of adolescence. Gene is a lonely, introverted intellectual. Phineas is a handsome, taunting, daredevil athlete. What happens between the two friends one summer, like the war itself, banishes the innocence of these boys and their world. A bestseller for more than thirty years, A Separate Peace is John Knowles's crowning achievement and an undisputed American classic.